Pengaruh Madu Dan Sari Kurma Terhadap Peningkatan Kadar Hemoglobin Pekerja Wanita Di Kantor UPP Bajoe - Damayanti, Alfina Defi; Hasriwiani Habo Abbas; Sumiaty (Window of Public Health Journal, 2024)
In Indonesia, cases of nutritional anemia reach 63.5%. In female workers, the prevalence of anemia is still quite high, namely around 30-46.6%. This can cause a decrease in work productivity, so that workers who suffer from anemia have 20% lower work productivity compared to healthy workers with good nutrition. Anemia that occurs in female workers is still quite high. 19% of female workers experience mild anemia, 50% moderate anemia and 8% severe anemia. The problem of anemia is caused by stress due to work, health problems due to economic factors, reproductive health problems and nutritional problems. One problem that can affect work productivity, especially among female workers, is nutritional anemia. The type of research used is quantitative using a quasi-experiment design with a one-group pretest-posttest design approach, namely by giving an initial test (pre-test) before being given treatment (education), then after being given treatment (education) a final test (post-test) is given. . The results of research from 24 respondents showed that there was a significant effect of giving honey and date palm juice on increasing hemoglobin levels. 15 ml dose of honey p=0.006 < 0.05, date palm juice p=0.007 < 0.05, and control group p=0.135 > 0.05. The most effective dose for increasing the Hb levels of female workers at the Bajoe Class II Port Organizing Unit Office, Bone Regency, is date juice at a dose of 1 spoon.